Rumble [videorecording (DVD)] - Grieve, Hamish; Lieberman, Matt, 1972-; Balfe, Lorne; Harrell, Rob (Paramount Home Entertainment, 2022)
Get ready for a unique, massively entertaining movie set in a world where monster wrestling is a global-sport, and superstar athletes are larger than life. When teenage Winnie teams up with a loveable underdog monster named Steve the Stupendous in hopes of training him to be a champion, the duo learn the value of moving to your own groove and paving your own unique path to success.